THE EFFECT OF ISLAMIC RELIGIOUS EDUCATION ON THE FORMATION OF GOOD MORALS IN STUDENTS OF MA SINAR HARAPAN - Al Amina, Agus Matin Aqna (Al-Mubin, 2025)
This study aims to determine the effect of Islamic Religious Education on the formation of noble morals in students at MA Sinar Harapan Talang Padang Tanggamus, Lampung. The background of this study is based on the importance of religious education in forming students' character and morals amidst the challenges of the globalization era. The approach used is quantitative with descriptive methods and simple linear regression analysis techniques. The research sample consisted of 113 grade XI students selected using the total sampling technique. The results of the analysis showed that there was a positive and significant influence between the variables of Islamic Religious Education (X) on the Formation of Noble Morals (Y). The coefficient of determination (R²) value was 0.409 or 40.9%, Islamic Religious Education contributed 40.9% to the formation of noble morals in students. The rest was influenced by other factors outside the variables studied. Thus, it can be concluded that Islamic Religious Education has an important role in forming noble morals in students